Formulation of Aromatherapy Balm from Essential Oil of Lemongrass (Cymbopogon citratus (DC.) Stapf) - La Ode Akbar Rasydy; Alasya Sihotang (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Lemongrass kitchen (Cymbopogon citratus (DC.) Stapf) is one type of spice native to Indonesia containing essential oil that can be used as perfumes, cosmetics, food additives and medicines. The study aims to formulate essential oils of lemongrass kitchen to aromatherapy balm preparations. Essential oils were obtained by steam distillation. The aromatherapy balm preparations were formulated by paraffin liquid, methanol, cera alba and vaseline album, and varying concentrations of essential oil of 0% (F1), 3% (F2), 6% (F3) and 12% (F4). The aromatherapy balms ware evaluated their physical quality with organoleptic tests, homogeneity tests, pH tests, GC-MS tests, and hedonic tests. Data were analyzed using one way ANOVA. The results showed that all aromatherapy balm formulas produced an organoleptic test that was yellowish white with a semi-solid form, smell like aromatherapy types. Homogeneity test showed F1-F4 did not change shape during storage. The pH test of the four formulas ranging from 5.27 to 6.89 met the skin neutral pH requirements. The preference test of 40 panelists showed that the panelists preferred the F4 which had a sharper aroma of aromatherapy essential oils. The results show that essential oil of lemongrass kitchen can be formulated to aromatherapy balm preparations with concentration of 12% of lemongrass, the best among the four formulas.